In Vitro Anticancer Activity of Mucoadhesive Oral Films Loaded with Usnea barbata (L.) F. H. Wigg Dry Acetone Extract, with Potential Applications in Oral Squamous Cell Carcinoma Complementary Therapy - Violeta Popovici; Elena Matei; Georgeta Camelia Cozaru; Laura Bucur; Cerasela Elena Gîrd; Verginica Schröder; Emma Adriana Ozon; Adina Magdalena Musuc; Mirela Adriana Mitu; Irina Atkinson; Adriana Rusu; Simona Petrescu; et al. (MDPI AG, 2022)
Oral squamous cell carcinoma (OSCC) is the most frequent oral malignancy, with a high death rate and an inadequate response to conventional chemotherapeutic drugs. Medical research explores plant extracts' properties to obtain potential nanomaterial-based anticancer drugs. The present study aims to formulate, develop, and characterize mucoadhesive oral films loaded with Usnea barbata (L.) dry acetone extract (F-UBA) and to investigate their anticancer potential for possible use in oral cancer therapy. U. barbata dry acetone extract (UBA) was solubilized in ethanol: isopropanol mixture and loaded in a formulation containing hydroxypropyl methylcellulose (HPMC) K100 and polyethylene glycol 400 (PEG 400). The UBA influence on the F-UBA pharmaceutical characteristics was evidenced compared with the references, i.e., mucoadhesive oral films containing suitable excipients but no active ingredient loaded. Both films were subjected to a complex analysis using standard methods to evaluate their suitability for topical administration on the oral mucosa. Physico-chemical and structural characterization was achieved by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Pharmacotechnical evaluation (consisting of the measurement of specific parameters: weight uniformity, thickness, folding endurance, tensile strength, elongation, moisture content, pH, disintegration time, swelling rate, and ex vivo mucoadhesion time) proved that F-UBAs are suitable for oral mucosal administration. The brine shrimp lethality (BSL) assay was the F-UBA cytotoxicity prescreen. Cellular oxidative stress, caspase 3/7 activity, nuclear condensation, lysosomal activity, and DNA synthesis induced by F-UBA in blood cell cultures and oral epithelial squamous cell carcinoma (CLS-354) cell line were investigated through complex flow cytometry analyses. Moreover, F-UBA influence on both cell type division and proliferation was determined. Finally, using the resazurin-based 96-well plate microdilution method, the F-UBA antimicrobial potential was explored against Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27353, Candida albicans ATCC 10231, and Candida parapsilosis ATCC 22019. The results revealed that each UBA-loaded film contains 175 µg dry extract with a usnic acid (UA) content of 42.32 µg. F-UBAs are very thin (0.060 ± 0.002 mm), report a neutral pH (7.01 ± 0.01), a disintegration time of 146 ± 5.09 s, and an ex vivo mucoadhesion time of 85 ± 2.33 min, and they show a swelling ratio after 6 h of 211 ± 4.31%. They are suitable for topical administration on the oral mucosa. Like UA, they act on CLS-354 tumor cells, considerably increasing cellular oxidative stress, nuclear condensation, and autophagy and inducing cell cycle arrest in G0/G1. The F-UBAs inhibited the bacterial and fungal strains in a dose-dependent manner; they showed similar effects on both Candida sp. and higher inhibitory activity against P. aeruginosa than S. aureus. All these properties lead to considering the UBA-loaded mucoadhesive oral films suitable for potential application as a complementary therapy in OSCC.